Rex the big dinosaur level 1 - Pitts, Sorrel (London : Ladybird books, 2017)
Rex is a big dinosaur. He sees some small dinosaurs. They are playing. "Can I play, too?" asks Rex
Keywords: English - Book; Ladybird - English